2019
DOI: 10.1037/xlm0000683
|View full text |Cite
|
Sign up to set email alerts
|

Mark my words: High frequency marker words impact early stages of language learning.

Abstract: High frequency words have been suggested to benefit both speech segmentation and grammatical categorization of the words around them. Despite utilizing similar information, these tasks are usually investigated separately in studies examining learning. We determined whether including high frequency words in continuous speech could support categorization when words are being segmented for the first time. We familiarized learners with continuous artificial speech comprising repetitions of target words, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 75 publications
(145 reference statements)
1
29
1
Order By: Relevance
“…However, this meant that infants were faced with the initial challenge of finding these items in the speech stream, which may have substantially increased the difficulty of the task [106,107]. It is possible that greater benefits to segmentation would emerge once high frequency words have reached a certain threshold of familiarity (perhaps with prior exposure, or with a longer training stream), thereby facilitating the interplay between top-down and bottom-up processing suggested in prior research [33,34] (see [45] for similar arguments). In future studies, measuring infants' knowledge of the high frequency words separately (and perhaps relating this to their performance on the segmentation task) would give valuable insight into this possibility.…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…However, this meant that infants were faced with the initial challenge of finding these items in the speech stream, which may have substantially increased the difficulty of the task [106,107]. It is possible that greater benefits to segmentation would emerge once high frequency words have reached a certain threshold of familiarity (perhaps with prior exposure, or with a longer training stream), thereby facilitating the interplay between top-down and bottom-up processing suggested in prior research [33,34] (see [45] for similar arguments). In future studies, measuring infants' knowledge of the high frequency words separately (and perhaps relating this to their performance on the segmentation task) would give valuable insight into this possibility.…”
Section: Plos Onementioning
confidence: 99%
“…In a recent study with adults, Frost, Monaghan, and Christiansen [ 45 ] examined the possibility that the benefit of high frequency words may actually be twofold—with these items potentially assisting with the categorisation of new words, in addition to helping with their initial discovery [ 46 49 ]. This was in light of the substantial overlap observed between the high frequency words that were seen to assist segmentation in the PUDDLE model [ 43 ] and words that were found to cue grammatical categorisation in prior corpus analyses [ 2 ] which indicated that the same items could conceivably inform learning for both tasks at the same time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations